PREPARATION AND CHARACTERIZATION OF IRON SULPHIDE THIN FILMS BY CHEMICAL BATH DEPOSITION METHOD - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2009)
ABSTRACT FeS2 thin films have been deposited by using low cost chemical bath deposition technique. The films obtained under deposition parameters such as bath temperature (90 GC),deposition period (90 min), electrolyte concentration (0.15 M) and pH of the reactive mixture (pH 2.5). The thin films were charaf